PENGARUH KEPEMIMPINAN TERHADAP KEPUASAN KERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI DI HOTEL KYRIAD BUMIMINANG - Windi Marta Syafutra; Youmil Abrian; Arif Adrian (Bogor Hospitality Journal, 2022)
This study aims to determine: 1) the influence of leadership on job satisfaction of hotel employees kyriad bumiminang. 2) the influence of the form of leadership on job satisfaction of kyriad bumiminang employees. 3) the influence of the form taken by the leadership on job satisfaction of kyriad bumiminang employees. This research was conducted with a quantitative approach with causal associative type. The population is all hotel employees with a total of 54 people, the sample is taken by distributing questionnaires or questionnaires with saturated sampling or the entire population is sampled.instrument, valid and reliable were conducted validity and reliability. The analytical test tool used is SmartPLS 3.0 with the SEM (Structural Equation Modeling) analysis method. This data analysis technique consists of testing the validity sample carried out by loading factor and average variance extracted (AVE) tests while reliability test internal consistency has a composite reliability that meets the criteria. This study shows that leadership has a positive effect on job satisfaction. Leadership has a positive effect on work motivation. Work motivation has a positive effect on job satisfaction. Leadership has a positive effect on job satisfaction with work motivation as a mediating variable. These results indicate that work motivation acts as partial mediation.